TINJAUAN ATAS PROSEDUR PEMUNGUTAN PAJAK BEA BALIK NAMA KENDARAAN BERMOTOR PADA KANTOR CABANG PELAYANAN DINAS PENDAPATAN PROVINSI JAWA BARAT WILAYAH KABUPATEN KUNINGAN (SAMSAT) 2012-2015 - Ade Suryana; Endro Andayani; Maharani Maharani (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2017)
One component of tax that greatly influences regional income is the tax on transfer of motor vehicle title (BBNKB). However, the perceptions and knowledge of taxpayers are not good enough about the procedure for collecting tax on transfer of motor vehicle names (BBNKB). The purpose of this study is to review the procedure for collecting motorbike name transfer tax at the branch office of the revenue service office in West Java Province, Kuningan District (SAMSAT). In collecting data, the writer does practical work, observation, interviews and documentation studies, the method that the writer does is descriptive method. From the results of the research and data collection conducted by the author, it was concluded that in collecting the Motor Vehicle Service Transfer Fee (BBNKB) branch of West Java Province Kuningan District (SAMSAT), there were still less optimal services so that there were still third parties (brokers). In the implementation of the payment. other than that, the perception and knowledge of the taxpayers' community is not good about the Fee for Transferring the Name of Motorized Vehicles.